A STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF DAUNORUBICIN AND CYTARABINE IN BULK AND PHARMACEUTICAL DOSAGE FORM - VENEELA, AKKALA SAI; RAJITHA, GALLA; NARIKIMALLI, ASHRITHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: A simple, accurate, and precise method was developed for the simultaneous estimation of daunorubicin and cytarabine dosage form using reverse-phase HPLC and validated with different parameters such as accuracy, precision, repeatability, linearity, limit of detection (LOD), and limit of quantitation (LOQ) as per ICH Q2R1 guidelines. Methods: The chromatogram was run through Agilent C18 Column of dimensions 150×4.6 mm, 5 m. Mobile phase containing 0.01N KH2PO4: Methanol taken in the ratio 50:50 was pumped through the column at a flow rate of 1.0 ml/min. The temperature was maintained at 30°C. The optimized wavelength selected was 240 nm. Results: Retention times for daunorubicin and cytarabine were found to be 2.433 min and 3.045 min. The %RSD of the daunorubicin and cytarabine was found to be 0.7 and 0.4, respectively. The %Recovery was obtained as 99.96% and 100.40% for daunorubicin and cytarabine, respectively. LOD and LOQ values obtained from regression equations of daunorubicin and cytarabine were 0.08 μg/ml, 0.24 μg/ml and 0.94 μg/ml, 2.86 μg/ml, respectively. The regression equation for daunorubicin is y=28587x+3141 and y=35995x+37534 for cytarabine. Conclusion: The method developed was simple and economical that can be adopted in regular quality control tests in industries.